The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/pbc.29491
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neuropsychological functioning in pediatric posterior fossa tumor survivors: Medulloblastoma, low‐grade astrocytoma, and healthy controls

Abstract: Background Neuropsychological comparison of medulloblastoma (MB) and cerebellar low‐grade astrocytoma (LGA) survivors to controls can clarify treatment‐related neurocognitive late effects. While both brain tumor groups undergo surgery to the posterior fossa, children with MB additionally receive craniospinal irradiation with boost and chemotherapy. This study provides an updated comparison of neuropsychological functioning in these two groups and examines effects of demographic risk factors upon outcomes. Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Our study, conducted on a fairly large sample of participants, confirms the results of other studies based on smaller samples showing that children who have survived cancer have cognitive and motor deficits [ 14 , 16 ]. Meanwhile, the large and varied clinical sample both in terms of the cancer survivor group and the control group could provide the solid rationale for improving and updating rehabilitation procedures aiming at restoring the neurocognitive and fine motor skills and potentially choosing the best pipeline for each individual patient, thus leading to potential improvements in cognitive outcomes and quality of life.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study, conducted on a fairly large sample of participants, confirms the results of other studies based on smaller samples showing that children who have survived cancer have cognitive and motor deficits [ 14 , 16 ]. Meanwhile, the large and varied clinical sample both in terms of the cancer survivor group and the control group could provide the solid rationale for improving and updating rehabilitation procedures aiming at restoring the neurocognitive and fine motor skills and potentially choosing the best pipeline for each individual patient, thus leading to potential improvements in cognitive outcomes and quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…A lot of research has demonstrated negative outcomes for pediatric brain cancer survivors, among which a decrease in cognitive, visual-motor, and visuospatial functioning were the most common [ 14 ]. This might be related to several factors: location of tumor as well as tumor origin and progression, type of therapy (for instance resection of a part of the brain for the pediatric cancer of the central nervous system), chemotherapy and radiation therapy, the consequences of treatment and hospitalization, age and time of the diagnosis, duration of treatment, and many other factors [ 15 , 16 , 17 ]. A systematic review showed that tumor histopathology and subsequent adjuvant therapy as well as the age of diagnosis influenced later neuropsychological difficulties in CNS tumor survivors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, studies of small samples of children and adolescents with craniopharyngioma have not demonstrated a relationship between excessive daytime sleepiness and cognitive outcomes such as attention and executive functions ( Jacola et al, 2016 ). A recent study identified a relationship between cognitive speed and fatigue among pediatric survivors of posterior fossa tumors ( Levitch et al, 2022 ), but this investigation did not isolate sleep disturbances as separate from fatigue. Sleep and fatigue are distinct concepts in pediatric oncology, with fatigue defined more as a lack of energy and feeling of exhaustion not necessarily associated with sleepiness ( Walter et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pediatric brain tumor survivors (PBTS) typically also have neurocognitive and behavioral problems [4][5][6][7][8][9]. Given that cranial radiotherapy (RT) is associated with a high risk of neurotoxicity in PBTS, many survivorship studies have focused on the cognitive outcomes of PBTS [8][9][10][11][12][13][14], but very few studies have investigated the neurobehavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%